2017
DOI: 10.24908/pceea.v0i0.6499
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Entrepreneurship on Engineering Education

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
0
12
0
3
Order By: Relevance
“…In US-based HEIs, the incorporation of engineering entrepreneurship in engineering curricula has quadrupled over the last three decades (Byers et al, 2013). Moreover, it was observed in Spain that “the idea of integrating entrepreneurship with engineering education seems to pick up whenever there is a volatile or gloomy forecast of the economy” (Jarrar and Anis, 2016: 1). The increasing rate of unemployment within major engineering functions (Barba-Sáncheza and Atienza-Sahuquillob, 2018) has drawn educators’ and policy-makers’ attention to the need to educate and equip students with an enterprising mindset from a young age (Mbuya and Schachtebeck, 2016, Wang and Wong, 2004).…”
mentioning
confidence: 99%
“…In US-based HEIs, the incorporation of engineering entrepreneurship in engineering curricula has quadrupled over the last three decades (Byers et al, 2013). Moreover, it was observed in Spain that “the idea of integrating entrepreneurship with engineering education seems to pick up whenever there is a volatile or gloomy forecast of the economy” (Jarrar and Anis, 2016: 1). The increasing rate of unemployment within major engineering functions (Barba-Sáncheza and Atienza-Sahuquillob, 2018) has drawn educators’ and policy-makers’ attention to the need to educate and equip students with an enterprising mindset from a young age (Mbuya and Schachtebeck, 2016, Wang and Wong, 2004).…”
mentioning
confidence: 99%
“…Implementing new curriculum courses and activities directly related to technology entrepreneurship would benefit the students. Formal courses in technology entrepreneurship [18] are also recommended, especially for those who are serious about entrepreneurship.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Various approaches have been used to integrate entrepreneurship into the curriculum for technical students, including specialized courses, for example, Technology Entrepreneurship for Engineers and Computer Scientists [18]; concentration and optional programs in leadership and innovation spanning a number of courses [7]; seminars and presentations on entrepreneurial experiences [7]. Recommendations to foster entrepreneurship among engineering university students include start-up exhibitions of successful entrepreneurs as role models, workshops on idea generation and business plan creation, and inter-university business plan competitions [4], and the inclusion of more female entrepreneurs as role models [8].…”
Section: Entrepreneurial Intentions and Entrepreneurship Educationmentioning
confidence: 99%
“…A recent study by Duke and HARVARD Universities over 500 technology companies revealed that only 37% of their leaders even have engineering backgrounds (Zwilling). If any country wants to have a sustained economic growth, educating engineers with entrepreneurial mindsets is absolutely necessary, specifically during the times of volatile economy (Jarrar, 2016). According to the report in 2012 by the World Intellectual Property Organization (INSEAD, 2012), the U.S. dropped to 10 th on a global innovation scale.…”
Section: Introductionmentioning
confidence: 99%